2017
DOI: 10.1021/acs.jmedchem.7b00164
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Study of Ghrelin(1–8) Resulting in High Affinity Fluorine-Bearing Ligands for the Ghrelin Receptor

Abstract: The ghrelin receptor, also known as the growth hormone secretagogue receptor 1a (GHS-R1a), is a G-protein-coupled receptor that is differentially expressed in healthy tissue and several cancers, including prostate, testicular, and ovarian. Selectively targeting the ghrelin receptor using fluorine-18 tagged entities would allow localization and visualization of ghrelin receptor expressing carcinomas using PET imaging. The endogenous ligand ghrelin, a 28 amino acid peptide with 3.1 nM affinity, has poor in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 36 publications
3
53
0
Order By: Relevance
“…This suggests that LEAP2 and ghrelin share a common ligand-binding pocket on GHSR1a. Previous studies demonstrated that the N-terminal fragment of ghrelin is essential for the binding and activation of GHSR1a [25,26]. The present study suggested that the N-terminal fragment of LEAP2 is important for binding to this receptor.…”
Section: Discussionsupporting
confidence: 65%
“…This suggests that LEAP2 and ghrelin share a common ligand-binding pocket on GHSR1a. Previous studies demonstrated that the N-terminal fragment of ghrelin is essential for the binding and activation of GHSR1a [25,26]. The present study suggested that the N-terminal fragment of LEAP2 is important for binding to this receptor.…”
Section: Discussionsupporting
confidence: 65%
“…These results correlate to those of the CD spectra, as the binding improves with increased α‐helicity. This relates to earlier findings that have noted that the first 5–8 amino acids are critical for receptor binding . Therefore modifying these positions to incorporate a lactam bridge would interfere with receptor recognition.…”
Section: Resultssupporting
confidence: 56%
“…We propose that an improved ghrelin imaging probe, for fluorescence imaging of ovarian cancer cells or tissue samples through the use of chemi‐staining or confocal microscopy, can be developed through the creation of stapled ghrelin analogues. Previous studies have shown that truncated fluorescently labelled ghrelin analogs, where the fluorescent dye is attached through a Lys ɛ‐amine of a modified ghrelin(1–19), provides a fluorescent probe with comparable GHS‐R1a affinity to that of natural ghrelin(1–28) and was demonstrated to bind to GHS‐R1a in cardiac tissues . This imaging probe was also used to distinguish between prostate cancer and benign hyperplasia in ex vivo prostate tissue and for in vivo biodistribution analysis .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations